(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
The ousting of autocrat Prime Minister Sheikh Hasina in August 2024, following a student-initiated mass uprising, marked a turning point in Bangladesh’s political trajectory and raised hopes for a national unity. The appointment of Nobel laureate Dr. Muhammad Yunus as Chief Advisor of the Interim Government was termed as ‘new beginning’ for a country plagued by authoritarian rule, political persecution, and systemic corruption. Yunu’s team elaborated their ‘new beginning’ – as one free from political persecution, discrimination, systematic corruption, and institutional decay. The Interim Government promised to initiate long-overdue legal reforms, political inclusivity, and bring an end to decades of authoritarian abuses. However, the promised transformation has largely failed to materialize. One year on, Bangladesh remains mired in cycles of revenge justice, mob violence, religious extremism, and fragile institutional governance. This article examines the limits of transitional reform process, arguing that the structural legacies of repression remain deeply embedded. Drawing on empirical development since the regime change, the article demonstrates how superficial political shifts have not addressed the entrenched practices of control and impunity. The article contributes to broader debates on transitional justice and democratization in South Asia by critically examining the illusion of meaningful reform in post authoritarian Bangladesh.